Pengaruh family class education (FaCE) terhadap pencegahan luka kaki diabetik - Yudi Akbar; Mursal Mursal; Feandi Putera; Ulan Sari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Diabetic foot ulcers (DFUs) are one of the most serious chronic complications of diabetes mellitus, leading to infection, amputation, reduced quality of life, and increased healthcare costs. Inadequate foot care practices and limited family involvement contribute to the high incidence of diabetic foot ulcers. FaCE is a family-based educational intervention designed to improve patients' knowledge, skills, and preventive behaviors through active family participation. Purpose: To determine the effect of FaCE on diabetic foot ulcer prevention in patients with diabetes mellitus. Method: This was a quasi-experimental study with a single-group pretest-posttest design. The study was conducted at a Community Health Center in Lhokseumawe City, involving 40 patients with type 2 diabetes mellitus selected using purposive sampling from a population of 80 patients. The FaCE intervention consisted of four educational sessions conducted over two weeks. Data were collected using a diabetic foot ulcer prevention behavior questionnaire developed based on the International Working Group on the Diabetic Foot (IWGDF) guidelines. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. Results: The median score for diabetic foot ulcer prevention behaviors increased from 19 at pre-test to 28 at post-test. Improvements were observed in all components of foot care, including daily foot examination, foot hygiene, skin moisturizing, nail care, protection against foot trauma, and appropriate footwear selection. The Wilcoxon signed-rank test demonstrated a statistically significant increase in diabetic foot ulcer prevention behaviors after the intervention (Z = −5.521; p < 0.001). Conclusion: FaCE has been shown to be effective in improving diabetic foot ulcer prevention behaviors in patients with diabetes mellitus. This family-based educational approach can be an effective health promotion and prevention strategy to reduce the risk of diabetic foot ulcers in primary care settings. Suggestion: The FaCE program can be integrated into chronic disease management programs or routine education programs at community health centers to increase family involvement in preventing diabetes complications. Future research is recommended to use a control group design, a larger sample size, and a longer follow-up period to evaluate the sustainability of behavioral changes and their impact on reducing the incidence of diabetic foot ulcers. Keywords: Diabetic Foot Ulcers; Diabetes Mellitus; Family Class Education.